TRANSPARANSI APBD SEBAGAI SARANA AKUNTABILITAS PUBLIK DAN GOOD GOVERNANCE - Fatmasari Sukesti; Alfasadun Alfasadun (Universitas Muhammadiyah Semarang, 2011)
Global crisis happened in Indonesia we have been aware of the importance of decentralization and regional autonomy in the real sense. The policy is based thinking to ensure efficiency, effectiveness, transparency, accountability and democratic values of the people in the exercise of government. The implications of such arrangements include the preparation of Revenue and Expenditure (APBD) and performance-based accountability and comprehensive financial reports as a form of accountability to check the Supreme Audit Agency (BPK). Arrangements and financial accountability is very urgent as a tool to bring transparency in public accountability for achieving good governance